Historiekunskap i årskurs 9 - Lars Berggren; Roger Johansson (Educare)
This report is part of the National evaluation of the Swedish compulsory school. The evaluation was conducted by the National Board of Education in 2003. The present report deals with pupils’ attitudes to History as a subject and to history education in the 9th grade. We have also made an evaluation of pupils’ knowledge of history. The survey shows that the majority of the pupils have positive views of history education and that they regard historical knowledge as important. The report highlights the importance of the teacher in the educational process. We also discuss the concept of historical consciousness and different ways of investigating the relationship between the past, the present and the future. One important aspect which is also discussed is the teaching of democratic values; in this context it is shown that pupils do not have sufficient knowledge about the democratic breakthrough.